Effects of railway track vibration induced by passing trains on an energy harvesting device - Cleante, Vinícius Germanos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
With advances in technology, and with the need to seek for solutions to reduce the effects of global warming, makes energy harvesting a popular research topic. The particular interest in this project is the harvesting of energy from ambient vibrations, which has applications in hostile environments or in remote areas. This type of device has the capacity feed microelectromechanical systems that use a low power, for example sensors for structural health monitoring, wireless sensors, radio communications, etc. In this work, an investigation is conducted to determine how much energy can be scavenged from vibrations due the passage of a train. A study is conducted to investigate the optimum parameters design of an energy harvester subject to vibrations induced by trains passing at different speeds. Vibration Data from two sites in the United Kingdom is used for this purpose. An approximate analytical expression for energy harvested from a linear harvester subject to a time-limited periodic excitation is evaluated using the harmonic components of the sleeper vibrations. The results are compared with those obtained through numerical analysis. Also, the behaviour of the linear energy harvester subject to vibrations induced by several passing trains is evaluated for ranges of speeds observed in measurement data sets at Steventon site

Com avanços em tecnologia, e com a necessidade em buscar soluções para reduzir efeitos do aquecimento global, tornou captação de energia uma área de pesquisa popular. O particular interesse deste projeto é a extração de energia a partir de vibrações em ambientes no qual possui aplicação em ambientes hostis ou em áreas remotas. Este tipo de dispositivo possui a capacidade de alimentar sistemas microeletrônicos que utilizam pouca energia, por exemplo sensores de monitoramento da saúde estrutural, sensores sem fio, radio comunicação, etc. Neste trabalho, uma investigação é conduzida para determinar a quantidade de energia que pode ser extraída a partir de vibrações devido a passagem do trem. Um estudo é conduzido para investigar o design dos parâmetros ótimos para um extrator de energia submetido a vibrações induzidas por trens passando com diferentes velocidades. Dados de vibração de dois locais no Reino Unido é utilizado para este propósito. Uma expressão analítica aproximada para energia extraída por um extrator linear submetido a excitação periódica de tempo limitado é avaliado utilizando os componentes harmônicos das vibrações em um dormente. Os resultados são comparados com os obtidos através da análise numérica. Também, o comportamento de um extrator de energia linear submetido a vibrações induzidas por diversos trens passantes, é avaliado para trens com uma faixa de velocidade observado nos dados mensurados em Steventon
Keywords: Energia - Armazenamento; Osciladores harmônicos; Vibração; Harmonic oscillators